ฟิล์มคอมพอสิตบริโภคได้จากโปรตีนถั่วเหลืองและเจลาตินปลาดัดแปรด้วยสารสกัดมะขามป้อมและการประยุกต์ในอาหาร - วรรณฉัตร สุขสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The objectives of this study were to investigate the effect of soy protein isolate-to-fish gelatin (SPI:GE) ratio as well as Indian gooseberry extract concentration on edible film properties and to evaluate the effect of the developed film on oxidative stability of a food product. In the first part of the study, the effect of SPI:GE ratio on film properties was explored. The SPI:GE ratio was varied as 100:0, 75:25, 50:50, 25:75, and 0:100. The fish gelatin film (0:100) was found to possess higher tensile strength than the soy protein film (100:0) (p≤0.05). In the case of composite films, the film with SPI:GE ratio of 25:75 demonstrated the greatest tensile strength, which was not significantly different from the fish gelatin film (p>0.05). As to elongation at break, it was found that the composite film with SPI:GE ratio of 25:75 had the highest elongation and this was significantly higher than the fish gelatin film (p≤0.05). The composite film was also similar in transparency, color, surface hydrophobicity, and water solubility to the fish gelatin film. However, the composite film displayed lower water vapor permeability than the fish gelatin film. Due to its superior mechanical properties, the composite film with SPI:GE ratio of 25:75 was thus selected to be studied in the next part. For the second part of the research, the effect of Indian gooseberry extract on properties of the selected composite film was investigated. The extract was varied at five different concentrations, i.e., 0, 2.5, 5.0, 7.5, and 10.0% by weight of protein. The composite film added with 5.0% Indian gooseberry extract exhibited the greatest tensile strength, which was 1.3 times higher than that of the control film without extract. The improvement in mechanical strength was a result of protein covalent cross-linking by C-N and C-S bonds, as confirmed using Fourier transform infrared spectroscopy and Raman microscopy. In terms of elongation at break, Indian gooseberry extract fortification resulted in a significant decrease in elongation of the composite film (p≤0.05). Moreover, it was found that extract addition produced a film with lower transparency and being yellow-orange in color with increasing chroma. The extract-added films also possessed higher water vapor permeability and surface hydrophobicity as compared to the unfortified control. Indian gooseberry extract incorporation also produced a film with higher total phenolic content as well as DPPH radical scavenging activity and ferric reducing antioxidant power. Owing to its highest tensile strength and antioxidant activity, the composite film with 5.0% Indian gooseberry extract was selected to be used in the next part. The application of the selected film to Chinese pork jerky (Bak Kwa) was carried out in the third part of the study. Three different samples were prepared: unwrapped jerky (control sample), jerky wrapped in nylon film (reference sample), and jerky wrapped in the composite film with SPI:GE ratio of 25:75 and added with 5.0% Indian gooseberry extract (experimental sample). The jerky samples were kept at room temperature (25ºC) for a period of 49 days. During storage, the jerky wrapped in the composite film showed significantly lower peroxide and TBARS values than the control sample (p≤0.05) but this was not different from the reference sample (p>0.05). In summary, this study demonstrated that the soy protein isolate-fish gelatin composite film modified with Indian gooseberry extract had improved tensile strength and antioxidant activity. Thus, it had a potential for retarding oxidation of a food product.